DPPH Radical Scavenging Potential of Ginger Leaves and Rhizomes - Barbosa, Gina Batoy; Peteros, Nonita Picardal (Asian Journal of Biological and Life Sciences, 2018)
Introduction: Gingers, belonging to the family Zingiberaceae, are popularly known for their beneficial uses in medicine and culinary applications. Aim: This study was conducted to evaluate the DPPH radical scavenging activity of the leaves and rhizomes of Zingiber officinale Rosc., Curcuma longa L., and Etlingera elatior (Jack) R.M. Smith. Methods: The plant samples were collected from Bukidnon, Mindanao, Philippines. Both water and ethanolic extracts were prepared separately from its leaves and rhizomes. The extracts were subjected to the determination of DPPH radical scavenging activity relative to ascorbic acid. Results and Discussion: Leaves, in general, had higher radical scavenging activity in water than in ethanol extracts. On the other hand, rhizomes had generally higher radical scavenging activity in ethanol than in water extracts except for E. elatior. Among the leaf extracts, E. elatior possessed the highest radical scavenging activity. In both water and ethanol, E. elatior displayed higher radical scavenging activity in its leaves that its rhizomes. Conclusion: Findings of this study suggest the potential of E. elatior leaves as source of antioxidants.
Keywords: Curcuma longa; DPPH; Etlingera elatior; Gingers; Zingiber officinale